2015
DOI: 10.1136/bmjqs-2015-004515
|View full text |Cite
|
Sign up to set email alerts
|

From the closest observers of patient care: a thematic analysis of online narrative reviews of hospitals

Abstract: Objective Patient-centred care has become a priority in many countries. It is unknown whether current tools capture aspects of care patients and their surrogates consider important. We investigated whether online narrative reviews from patients and surrogates reflect domains in the Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) and we described additional potential domains. Design We used thematic analysis to assess online narrative reviews for reference to HCAHPS domains and salie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 43 publications
2
39
0
1
Order By: Relevance
“…In healthcare, this means patients, staff, managers and others. ‘Mapping out’ the system relies on asking participants the right questions in the right way , or, alternatively, asking these questions in the thematic analysis of transcript data, reviews and other sources of insight 18–20…”
Section: Overview Of Support: the Sim And Supporting Toolsmentioning
confidence: 99%
“…In healthcare, this means patients, staff, managers and others. ‘Mapping out’ the system relies on asking participants the right questions in the right way , or, alternatively, asking these questions in the thematic analysis of transcript data, reviews and other sources of insight 18–20…”
Section: Overview Of Support: the Sim And Supporting Toolsmentioning
confidence: 99%
“…Other work has also suggested that patients' friends and family members are an important source of information about safety concerns. 20,21 In addition, several patient characteristics were associated with an increased likelihood of reporting a breakdown, including being younger and better educated. These findings highlight the importance of engaging patients' friends and families in efforts to elicit patient concerns about healthcare, and they confirm recommendations for patients to bring a friend or family member to healthcare encounters.…”
Section: Discussionmentioning
confidence: 99%
“…Social media websites such as Yelp and Facebook enable all patients to share their experiences, not just the limited sample that receives a survey. Family members and friendsnot just patients themselvescan also comment on these sites, potentially providing additional useful information (Bardach et al 2016). Social media websites also allow immediate reporting, thereby eliminating the considerable delays that occur with traditional survey methods.…”
Section: Contrast With Other Methods Of Collecting Patient Experiencementioning
confidence: 99%